Poetic Symbol of Hussein Jenkir - Kawthar Shakir Abdul Redha, Asst.Lect. (lark, 2023)
Symbolism in the literary arena constitutes an expressive approach to conveying emotions, sensations, and sentiments through the use of implication and indication. Symbols often manipulate words in a distinctive manner, deviating from the ordinary. This aligns with the nature of poetry inclined towards realms of mystery and ambiguity. Consequently, symbolic images in poetry may initially be unclear, gradually acquiring independent symbolic significance, thereby dispelling the initial ambiguity. Hussein Jankir’s poetry exemplifies a harmonious integration with the use of symbolism. It distinctly manifests through his employment of symbolic nuances, positioning symbolism as a fundamental element in the construction of his poems. This highlights his ability to transform symbols into aesthetic tools that elevate the uniqueness of his poetic voice, providing depth to its interpretations.